The dragon's gate - Wolverton, Barry (Wolverton, Barry. Chronicles of the black tulip, 2017)
When Bren and Mouse discover treasure and a map buried on the Vanishing Island, Mouse is determined to follow the map to the Dragon's Gate, hoping it will explain who she really is.